Assessment of Physico-Chemical Properties of the Pasur River Estuarine Water - Shefat, SHT; Chowdhury, MA; Haque, F; Hasan, J; Salam, MA; Shaha, DC (Annals of Bangladesh Agriculture, 2021)
This study aimed to investigate physico-chemical properties of the Pasur River Estuarine (PRE) water connected to the Sundarbans mangrove ecosystem during the dry season for examining the ecosystem health. In-situ measurement and water sample collection were performed to assess physico-chemical properties at fifteen sampling stations along the main axis of the estuary in March 2018, April 2018, January 2019 and March 2019. Surface water temperature ranged from 20.7 to 33.7°C, pH from 7.1 to 7.9, and salinity from 8.5 to 16.2 PSU (practical salinity unit). Dissolved Oxygen (DO) concentration varied from 5.9 to 8.4 mg/L. Ammonium-nitrogen (NH4 +) was the dominant nitrogenous compound among the dissolved inorganic nitrogenous (NH4 + +NO3 -+NO2 -) compounds, and ranged from 0.11 to 2.11 mg/L. Higher NH4 + concentration in water column was largely attributed to release by tidal wash-out of the interstitial waters of the surﬁcial mangrove sediments. In contrast, phosphate concentration varied from 0.07 to 5.8 mg/L. The Pearson correlation coefficient was calculated to elucidate the correlation among physico-chemical properties during the dry season. Temperature showed a significant positive correlation with salinity and total dissolved solids (TDS), and negative correlation with DO. Similarly, salinity showed a significant positive correlation with TDS and negative correlation with DO. According to the Redfield ratio, the PRE is a nitrogen-limited estuarine system during the dry season. Ann. Bangladesh Agric. (2020) 24(1) : 1-16